2021
DOI: 10.1002/ejic.202001072
|View full text |Cite
|
Sign up to set email alerts
|

From Missing Links to New Records: A Series of Novel Polychlorine Anions

Abstract: Herein we report the synthesis and structural characterization of four novel polychloride compounds. The compounds [CCl(NMe2)2][Cl(Cl2)3] and [NPr4][Cl(Cl2)4] have been obtained from the reaction of the corresponding chloride salts with elemental chlorine at low temperature. They are the missing links in the series of polychloride monoanions [Cl(Cl)n]− (n=1–6). Additionally, the reaction of decamethylferrocene with elemental chlorine was studied yielding [Cp*2Fe]2[Cl20], which contains the largest known polych… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Raman spectra of single crystals were recorded at −196 °C using a Bruker RamanScope III spectrometer with a Laser power of 450 mW and 256 scans with a resolution of 4 cm −1 . The samples were measured using a Teflon plate that is cooled by a liquid nitrogen cooled copper block, producing a nitrogen atmosphere that kept the sample inert [58] . IR spectra were measured at room temperature under an argon stream using a Nicolet iS50 FTIR spectrometer with a diamond ATR attachment with 32 scans and a resolution of 4 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectra of single crystals were recorded at −196 °C using a Bruker RamanScope III spectrometer with a Laser power of 450 mW and 256 scans with a resolution of 4 cm −1 . The samples were measured using a Teflon plate that is cooled by a liquid nitrogen cooled copper block, producing a nitrogen atmosphere that kept the sample inert [58] . IR spectra were measured at room temperature under an argon stream using a Nicolet iS50 FTIR spectrometer with a diamond ATR attachment with 32 scans and a resolution of 4 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The samples were measured using a Teflon plate that is cooled by a liquid nitrogen cooled copper block, producing a nitrogen atmosphere that kept the sample inert. [58] IR spectra were measured at room temperature under an argon stream using a Nicolet iS50 FTIR spectrometer with a diamond ATR attachment with 32 scans and a resolution of 4 cm À 1 . For the MIR spectra (4000-400 cm À 1 ), a KBr beam splitter was used, while for the FIR spectra (600-50 cm À 1 ), a polyethylene beam splitter was used.…”
Section: Materials Chemicals and Proceduresmentioning
confidence: 99%
“…At the outset of this work, we anticipated that organic chloride salts can reversibly bind chlorine by forming polychlorides (also known as polychlorine anions). Due to their large structural diversity and possible applications, 15 Polychlorides with lower chlorine content exist either as solids or as low viscous ionic liquids (Figure 2) with a significantly reduced vapor pressure compared to Cl 2 gas. This makes them easy-to-handle chlorination reagents that have been used in numerous organic transformations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to their large structural diversity and possible applications, polychloride salts received much attention in recent years . It was shown that a complete row of polychlorine monoanions [Cl­(Cl 2 ) n ] − with n = 1–6 can be stabilized using weakly coordinating cations (e.g., PPh 4 or NPr 4 ), while the recently reported [Cl 20 ] 2– represents the largest known polychloride . Polychlorides with lower chlorine content exist either as solids or as low viscous ionic liquids (Figure ) with a significantly reduced vapor pressure compared to Cl 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…However, direct reaction of ferrocenes with elemental halogens is often synthetically not useful to prepare halogenated derivatives. Instead, one-electron oxidation to ferrocenium cations or total decomposition is typically observed . Therefore, monohaloferrocenes FeC 10 H 9 X (X = F, Cl, Br, I) are instead synthesized by monometalation followed by quenching with an electrophilic halogenation agent. Higher halogenation degrees (FeC 10 H n X 10– n ; n = 2–8) lead to a large number of possible isomers.…”
Section: Introductionmentioning
confidence: 99%